ANSWER:
![\begin{gathered} \:\sqrt[4]{4}cis\left(-(\pi )/(24)\right)\: \\ \\ \:\sqrt[4]{4}cis\left((11\pi)/(24)\right)\: \\ \\ \:\sqrt[4]{4}cis\left((23\pi)/(24)\right)\: \\ \\ \:\sqrt[4]{4}cis\left((35\pi)/(24)\right)\: \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/wtvt2zsxqrqqyz82t3vst0d46jbh0wmbl9.png)
Explanation:
We have the following expression:
![2√(3)-2i](https://img.qammunity.org/2023/formulas/mathematics/college/fjwplpdn1oyjdj9kdefek7un1rbh2ecnjf.png)
To calculate the 4 roots we must match the equation with x raised to 4, just like this:
![x^4=2√(3)-2i](https://img.qammunity.org/2023/formulas/mathematics/high-school/1wj3uva8qqwp7k7bg4g9kbb5cv0ac5n6d3.png)
For this case the roots are given as follows:
![\begin{gathered} \:z_k=\sqrt[n]a\right\left(\cos\left((\arctan\left(\alpha\right)+2k\pi)/(n)\right)+i\sin\left((\arctan\left(\alpha\right)+2k\pi)/(n)\right)\right) \\ \\ \text{ In this case:} \\ \\ n=4 \\ \\ |a|=\sqrt{\left(2√(3)\right)^2+\left(-2\right)^2}=√(12+4)=√(16) \\ \\ a=4 \\ \\ \alpha=\left((-2)/(2√(3))\right) \\ \\ \text{ Therefore:} \\ \\ \arctan\left((-2)/(2√(3))\right)=-(\pi)/(6) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/cydyk1ch6cnz30nwv9ddqay1nm5qk7lqdh.png)
Taking into account the above, we calculate for each x,
when k = 0,1, 2 3, just like this:
![\begin{gathered} x_1=\sqrt[4]{4}\left(\cos\left((-(\pi)/(6)+2\cdot\:0\pi)/(4)\right)+i\sin\left((-(\pi)/(6)+2\cdot\:0\pi)/(4)\right)\right)=\sqrt[4]{4}\left(\cos\left(-(\pi)/(24)\frac{}{}\right)+i\sin\left(-(\pi)/(24)\right)\right)=\sqrt[4]{4}cis\left(-(\pi)/(24)\right) \\ \\ x_2=\sqrt[4]{4}\left(\cos\left((-(\pi)/(6)+2\cdot\:1\pi)/(4)\right)+i\sin\left((-(\pi)/(6)+2\cdot\:1\pi)/(4)\right)\right)=\sqrt[4]{4}\left(\cos\left((11\pi\:)/(24)\right)+i\sin\left((11\pi\:)/(24)\right)\right)=\:\sqrt[4]{4}cis\left((11\pi\:)/(24)\right)\: \\ \\ x_3=\sqrt[4]{4}\left(\cos\left((-(\pi)/(6)+2\cdot\:2\pi)/(4)\right)+i\sin\left((-(\pi)/(6)+2\cdot\:2\pi)/(4)\right)\right)=\sqrt[4]{4}\left(\cos\left((23\pi\:)/(24)\right)+i\sin\left((23\pi\:)/(24)\right)\right)=\sqrt[4]{4}cis\left((23\pi\:)/(24)\right)\: \\ \\ x_4=\sqrt[4]{4}\left(\cos\left((-(\pi)/(6)+2\cdot\:3\pi)/(4)\right)+i\sin\left((-(\pi)/(6)+2\cdot\:3\pi)/(4)\right)\right)=\sqrt[4]{4}\left(\cos\left((35\pi\:)/(24)\right)+i\sin\left((35\pi\:)/(24)\right)\right)=\:\sqrt[4]{4}cis\left((35\pi\:)/(24)\right)\: \end{gathered}]()